Different Doses of ?-Cryptoxanthin May Secure the Retina from Photooxidative Injury Resulted from Common LED Sources - Orhan, Cemal; Tuzcu, Mehmet; Gencoglu, Hasan; Sahin, Emre; Şahin, Nurhan; Ozercan, Ibrahim Hanifi; Şahin, Kazım (Hindawi Ltd, 2021)
Retinal damage associated with loss of photoreceptors is a hallmark of eye diseases such as age-related macular degeneration (AMD) and diabetic retinopathy. Potent nutritional antioxidants were previously shown to abate the degenerative process in AMD. beta-Cryptoxanthin (BCX) is an essential dietary carotenoid with antioxidant, anti-inflammatory, and provitamin A activity. It is a potential candidate for developing intervention strategies to delay the development/progression of AMD. In the current study, the effect of a novel, highly purified BCX oral formulation on the rat retinal damage model was evaluated. Rats were fed with BCX for four weeks at the doses of 2 and 4 mg/kg body weight in the form of highly bioavailable oil suspension, followed by retinal damage by exposing to the bright light-emitting diode (LED) light (750 lux) for 48 hrs. Animals were sacrificed after 48 hours, and eyes and blood samples were collected and analyzed. BCX supplementations (2 and 4 mg/kg) showed improvements in the visual condition as demonstrated by histopathology of the retina and measured parameters such as total retinal thickness and outer nuclear layer thickness. BCX supplementation helped reduce the burden of oxidative stress as seen by decreased serum and retinal tissue levels of malondialdehyde (MDA) and restored the antioxidant enzyme activities in BCX groups. Further, BCX supplementation modulated inflammatory markers (IL-1 beta, IL-6, and NF-kappa B), apoptotic proteins (Bax, Bcl-2, caspase 3), growth proteins and factors (GAP43, VEGF), glial and neuronal proteins (GFAP, NCAM), and heme oxygenase-1 (HO-1), along with the mitochondrial stress markers (ATF4, ATF6, Grp78, Grp94) in the rat retinal tissue. This study indicates that oral supplementation of BCX exerts a protective effect on light-induced retinal damage in the rats via reducing oxidative stress and inflammation, also protected against mitochondrial DNA damage and cellular death.